Relationship between bacteria-induced endometritis and subfertility in Peruvian Paso mares - Chávez Chávez, Elsa (2025)
The objective of this study was to determine the relationship between enterobacteria-induced endometritis and subfertility in Peruvian Paso mares. A total of 38 cyclic females, aged 5 to 15 years and raised in stud farms in Lima, Cañete, and Chincha, were evaluated.  Nineteen mares were assigned to the control group (healthy), and the remaining 19 mares constituted the case group (subfertile). Uterine mucosa samples were collected on day 2 of estrus for bacterial culture and cytology using uterine brushing. Endometritis of varying degrees was diagnosed in 100% of the subfertile mares. Post-mating endometritis (PME), previous antimicrobial treatment, and the number of artificial inseminations per season were factors associated with subfertility. The main bacterial species and genera isolated were Bacillus sp. (36.8%), Staphylococcus sp. (26.3%), Escherichia coli (18.4%), Klebsiella sp. (13.2%), and Citrobacter sp. (7.9%). The presence of positive bacterial cultures was not related to subfertility. The results demonstrate that endometritis, regardless of its etiology, is one of the main factors associated with subfertility in these mares.